Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2010
DOI: 10.1145/1753326.1753388
|View full text |Cite
|
Sign up to set email alerts
|

Children's roles using keyword search interfaces at home

Abstract: Children want to find information about their world, but there are barriers to finding what they seek. Young people have varying abilities to formulate complex queries and comprehend search results. Challenges in understanding where to type, confusion about what tools are available, and frustration with how to parse the results page all have led to a lack of perceived search success for children 7-11 years old. In this paper, we describe seven search roles children display as information seekers using Internet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 9 publications
1
68
0
Order By: Relevance
“…Over-16s also played around 10 games on average, and produced more queries per game than under16s. These usage statistics suggest that adults are capable of forming search queries much more quickly than children -this is consistent with previous findings [3]. Also, younger children were inclined to play more games of PageFetch each than adults were suggesting that the incentive or the design of the game was appealing.…”
Section: Results and Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…Over-16s also played around 10 games on average, and produced more queries per game than under16s. These usage statistics suggest that adults are capable of forming search queries much more quickly than children -this is consistent with previous findings [3]. Also, younger children were inclined to play more games of PageFetch each than adults were suggesting that the incentive or the design of the game was appealing.…”
Section: Results and Analysissupporting
confidence: 89%
“…When considering the results of each experiment, users were divided into three age brackets -under-12s, 12 -16 year olds, and over-16s. These brackets were based on previous groupings used in children's information retrieval studies [3,5]. Table 4 provides a summary of the usage statistics for the di↵erent age groups.…”
Section: Pilot Studymentioning
confidence: 99%
See 1 more Smart Citation
“…When designing for the ubiquity of search in our own foray into studying children's search practices on the internet [15,23], we discovered that in-context design and testing is crucial. Children search in their home or school environments, not in contrived lab settings.…”
Section: Guidelines For Designing For Ubiquity Of Searchmentioning
confidence: 99%
“…Based on the result, he claimed that the system design suitable for children and Web training are important because children have difficulty in keyword searching. Druin et al [3] conducted a home study of 83 children using Web search engines. As the result, they found that children can be classified into seven groups in terms of their searching activities, e.g., children who are familiar with PCs and succeed in search, and children who have a strong motivation in search but fail it.…”
Section: Related Workmentioning
confidence: 99%